Case report: Strong low-density-cholesterol reduction accompanied by shrinkage of low-attenuation coronary plaque during lipid-lowering treatment with bempedoic acid—serial evaluation by coronary computed tomography angiography - Korosoglou, Grigorios; Giesen, Alexander; Geiss, Eva; Stach, Ksenija (Frontiers in Cardiovascular Medicine, 2023)
Herein we present a patient with coronary artery disease and prior percutaneous coronary interventions. In this patient, multiple statins and ezetimibe had to be discontinued due to intolerance with musculoskeletal complaints and nausea. Monotherapy with bembedoic acid was well tolerated and achieved exceptionally effective lipid-lowering, so that the LDL target of <55mg/dl could be successfully reached, as recommended by current guidelines. In addition, serial coronary computed tomography angiography (CCTA) performed upon clinical indications, during 20 months of lipid-lowering treatment with bembedoic acid, demonstrated signs of favorable plaque component modification, with shrinkage of low-attenuation plaque component compared to baseline findings.